Strategi Pengembangan Keterampilan Public Speaking dalam Meningkatkan Kompetensi Guru Pendidikan Agama Islam - Choirunnisa, Fitra Nur; Sukmawati, Anis (Proceedings of Annual Islamic Conference for Learning and Management, 2024)
This research is a library research study which aims to analyze and present an in-depth understanding of public speaking training strategies in the context of increasing the competency of Islamic Religious Education (PAI) teachers. PAI teachers have a major role in forming understanding of the Islamic religion among students. Therefore, their ability to communicate and convey religious material effectively is crucial. This research focuses on analyzing literature and previous studies that are relevant to the topic of implementing public speaking training for PAI teachers. Data was collected through searching and analyzing scientific articles, books, journals and other academic sources related to public speaking training strategies and religious education. The results of this research include the development of public speaking skills, which is important for increasing PAI teachers’ competence in conveying material effectively, creating interactive learning, and being a role model for good communication. These skills strengthen teacher professionalism, help students understand Islamic teachings, and support the formation of students’ character and missionary competence. This strategy contributes directly to improving the quality of PAI learning and the quality of education